26th International Conference on Intelligent User Interfaces 2021
DOI: 10.1145/3397481.3450659
|View full text |Cite
|
Sign up to set email alerts
|

Do You Have Time for a Quick Chat? Designing a Conversational Interface for Sexual Harassment Prevention Training

Abstract: Sexual harassment (SH) incidents are increasing and call into question the effectiveness of traditional SH prevention training. In this paper, we introduce a proof-of-concept design of a conversational interface (CI) for understanding SH cases. Key features of the interface include that it engages the learner in a dyadic conversation, prompts the learner for guidance, and tells a story of SH from a first-person perspective. From a mixed-methods study (N=32), learners experiencing a SH vignette using the conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The self-reported data also reveals a negative correlation between the time spent on Facebook chat and studying for classes. Overuse of chat may constitute a distraction for learning, as stated by Do, Yang, Choi, Fu, and Bailey (2021), who found that students who did not set aside enough time for study did so because of chat.…”
Section: Student Perceived Learning Experiencementioning
confidence: 99%
“…The self-reported data also reveals a negative correlation between the time spent on Facebook chat and studying for classes. Overuse of chat may constitute a distraction for learning, as stated by Do, Yang, Choi, Fu, and Bailey (2021), who found that students who did not set aside enough time for study did so because of chat.…”
Section: Student Perceived Learning Experiencementioning
confidence: 99%
“…This tutorial is fundamentally relevant to the IUI community owing to its relation to intelligent conversational interfaces. More recently, researchers in IUI have been drawn to investigate CUIs for a variety of application domains, including learning a second language [25], sexual harassment prevention [5], qualitative interviews [3], and music production [4], among others. Furthermore, this tutorial will emphasize the distinctive characteristics of CUIs, ushering the IUI community to redefine and expand the scope of CUIs.…”
Section: Relevance Of Conversational User Interfacesmentioning
confidence: 99%